2012
DOI: 10.1002/bdra.23045
|View full text |Cite
|
Sign up to set email alerts
|

Maternal occupational exposure to polycyclic aromatic hydrocarbons and risk of neural tube defect‐affected pregnancies

Abstract: BACKGROUNDThis study evaluated whether there is an association between maternal occupational exposure to polycyclic aromatic hydrocarbons (PAHs) and neural tube defects (NTDs) in offspring. This is the first such study of which the authors are aware.METHODSData were analyzed from 1997 to 2002 deliveries in the National Birth Defects Prevention Study, a large population‐based case‐control study in the United States. Maternal interviews yielded information on jobs held in the month before through 3 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
2
43
0
2
Order By: Relevance
“…Maternal occupational exposure to PAHs was associated with increased risks of congenital heart defects (Lupo et al, 2012b), gastroschisis (Lupo et al, 2012a) and NTDs (Langlois, Hoyt, 2012). In our previous study, maternal passive smoking and exposure to indoor coal combustion had been shown to be associated with an elevated NTD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal occupational exposure to PAHs was associated with increased risks of congenital heart defects (Lupo et al, 2012b), gastroschisis (Lupo et al, 2012a) and NTDs (Langlois, Hoyt, 2012). In our previous study, maternal passive smoking and exposure to indoor coal combustion had been shown to be associated with an elevated NTD risk.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory animals, embryos exposed to derivatives of PAHs have been shown to present with NTDs (Barbieri et al, 1986, Incardona et al, 2004). Human studies have also indicated that maternal prenatal exposure to PAHs was associated with an elevated risk for NTDs in offspring, using residence location or biomarkers of exposure (Demetriou et al, 2012, Langlois et al, 2012, Rankin et al, 2009). Previously we demonstrated that indoor air pollution from coal combustion was a potential risk factor for NTDs in Shanxi Province, where the concentration of PAHs emissions is amongst the highest in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Several derivatives of PAHs have been shown to be teratogenic in animal models, producing NTDs and a variety of other malformations in the exposed embryos [5]. There is also growing evidence from human environmental and occupational studies on risks of NTDs in association with prenatal exposure to PAH [6-9]. PAHs can exert genotoxic effects through metabolic activation and subsequent binding to DNA, thus forming bulky PAH-DNA adducts, a widely used indicator of DNA damage that has been associated with increased cancer risk [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…This expert review strategy was based on an approach previously developed and used in the Baltimore-Washington Infant Study (Jackson et al, 2004) and described previously (Langlois et al, 2012). Specifically, as part of the NBDPS occupational exposure assessment, industrial hygienists involved in the project participated in a training session before reviewing the job histories.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, studies in humans suggest maternal occupational and environmental exposure to PAHs is associated with structural birth defects including neural tube defects (Naufal et al, 2010; Ren et al, 2011; Langlois et al, 2012) and gastroschisis (Lupo et al, 2012). Despite this evidence, to our knowledge there have been no studies evaluating the potential association between maternal occupational exposure to PAHs and CHDs among offspring.…”
Section: Introductionmentioning
confidence: 99%